Pemberdayaan Petani Garam Melalui Inovasi Sabun Cuci Piring Berbasis Garam dan Branding Produk Lokal - Prajaputra, Vicky; Vonna, Adinda Gusti; Fakri, Fajar; MC, Ulil Amri; Isnaini, Nadia; Panggabean, Dara Meutia; Rezkina, Cutwan Annura; Putri, Rizka Auriza; Musfira, Rifqi; Nurzima; Arifqi, Muhammad; Azizah, Nurfiah; Jannah, Raudhatul; Shahieza, Najmi Dibya; Firzatullah, Muhammad Nabil (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
This community empowerment program aims to enhance the capacity and welfare of Kuala Gigieng salt farmers through the innovation of salt-derived products and the strengthening of product branding. The activities were carried out at the Training Center of Universitas Syiah Kuala and in Gampong Neuheun, Aceh Besar District, using a participatory training approach. The stages included socialization, training on the production of salt-based dishwashing soap, practice in crushing and packaging refined salt, business management assistance, and evaluation through pre-test and post-test. The pre-test results showed that most participants had limited understanding of soap making, branding, and business management (≥50% in the poor category). After the training, significant improvements were recorded: 62.29% of participants demonstrated excellent understanding of soap production, 78.57% understood tools and ingredients, 85.71% understood branding and marketing, and 100% expressed very high interest in the program. The dishwashing soap produced was characterized by good foaming quality, effective cleaning ability, and a fresh aroma from patchouli oil. In addition, raw salt was successfully processed into 250 g packaged refined salt under the brand Merak Bintang Global, which increased its market value by approximately 40% compared to bulk salt. Business management assistance also encouraged the establishment of simple financial records and a clearer organizational structure within the farmer group.